Pacing strategy of a full Ironman overall female winner on a course with major elevation changes - Pryor, J. L.; Adams, W. M.; Huggins, R. A.; Belval, L. N.; Pryor, R. R.; Casa, D. J. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to use a mixed-methods design to describe the pacing strategy of the overall female winner of a 226.3-km Ironman triathlon. During the race, the triathlete wore a global positioning system and heart rate (HR)-enabled watch and rode a bike outfitted with a power and cadence meter. High-frequency (every km) analyses of mean values, mean absolute percent error (MAPE), and normalized graded running pace and power (accounting for changes in elevation) were calculated. During the bike, velocity, power, cadence, and HR averaged 35.6 km/h, 199 W, 84 rpm, and 155 b/min, respectively, with minimal variation except for velocity (measurement unit variation [MAPE]: 7.4 km/h [20.3%], 11.8 W [7.0%], 3.6 rpm [4.6%], 3 b·min-1 [2.3%], respectively). During the run, velocity and HR averaged 13.8 km/h and 154 b/min, respectively, with velocity varying four-fold more than HR (MAPE: 4.8% vs. 1.2%). Accounting for elevation changes, power and running pace were less variable (raw [MAPE] vs. normalized [MAPE]: 199 [7.0%] vs. 204 W [2.7%]; 4:29 [4.8%] vs. 4:24 min/km [3.6%], respectively). Consistent with her planned pre-race pacing strategy, the triathlete minimized fluctuations in HR and watts during the bike and run, whereas velocity varied with changes in elevation. This case report provides observational evidence supporting the utility of a pacing strategy that allows for an oscillating velocity that sustains a consistent physiological effort in full Ironman races.